ANALYSIS OF THE EFFECT OF MURABAHAH FINANCING ON PROFITABILITY WITH NON PERFORMING FINANCING (NPF) AS AN INTERVENING VARIABLE IN BTPN SYARIAH - Putri, Sonia; Maulana, Chandra Zaky; Ramayanti, Tariza Putri (Jurnal Manajemen, 2024)
ROA is a description of a bank's ability to generate profits. Increasing the ROA of a bank is very important for investors' interests because it can influence investors' confidence in continuing to invest or save at the bank. ROA is influenced by financing and the rate of return on the financing itself, therefore banks must always pay attention to providing financing so as not to increase the amount of non-performing financing (NPF) which can affect ROA. This research aims to determine the effect of murabahah financing on profitability with non-performing financing (NPF) as an intervening variable at BTPN Syariah bank. This research uses quantitative research with secondary data obtained from quarterly financial reports published on the BTPN Syariah bank website for the 2015-2022 period. This research used a saturated sampling technique with predetermined criteria resulting in 32 samples with an observation period of 8 years. The data analysis technique uses path analysis with SPSS 20 tools.The results of this research data analysis prove that murabahah financing has a significant effect on NPF, murabahah financing has a significant effect on ROA, NPF has no effect on ROA, NPF is unable to mediate the effect of murabahah financing on ROA.